Caribbean Report 12-03-1990 - Crosskill, Hugh (anchor); Thompson, Alan (correspondent); De Ronceray, Hubert (interviewee); Bell, Stephen (analyst); Goffe, Leslie (correspondent); Jones, Ben (interviewee); Brathwaite, Nicholas (interviewee); Mitchell, Keith (interviewee); Gairy, Eric (interviewee); Emmanuel, Patrick (interviewee); Saunders, Nick (interviewee); Edwards, Andy (correspondent) (The British Broadcasting Corporation, 1990)
Deposed military leader, General Prosper Avril flew into exile this morning aboard an American military plane after days of violent unrest and demonstrations. The toppled government clears the way for the appointment of the country’s first woman president, Ertha Pascal-Trouillot of the Haitian Supreme Court. Irate protesters call on the United States to deport General Avril back to Haiti to face a trial. Following the Financial News, the Grenadians go to the polls tomorrow and the report explores the possibility of a coalition government if no one party wins a majority. The final segment addresses the future coaching and political plans of Nick Sauders, Bermuda’s high jumper who won the men’s high jump title at the British National Indoor Championships.
1. Headlines (00:00-01:25)
2. Haitian President, General Prosper Avril exiled in the United States after his resignation on Saturday, paving the way for the appointment of an interim president. Alan Thompson reports from Port-au-Prince, includes an interview with Hubert De Ronceray (01:26-06:21)
3. Financial News. Stephen Bell, currency analyst, comments on the value of the sterling on the financial markets (06:22-08:01)
4. Grenada holds general elections tomorrow. Leslie Garth interviews the heads of the major political parties on the chances of a coalition government, including an interview with Dr. Patrick Emmanuel, Institute of Social and Economic Research, UWI, Cave Hill (08:02-13:19)
Keywords: Haiti -- Politics and government.; Avril, Prosper -- Expulsion.; Pascal-Trouillot, Ertha.; Women -- Political activity -- Haiti.; Elections -- Grenada.; Grenada -- Politics and government.; Athletes -- Bermuda Islands.; Coalition governments -- Haiti.; Grenada National Party.; National Democratic Congress Party -- Grenada.; New National Party -- Grenada.; Grenada United Labour Party.